Sericea Lespedeza and the Future of Invasive Species, A Symposium With a Look to the Future - Ohlenbusch, Paul (My University, 2000)
This publication provides information about sericea lespedeza and disucsses the invasiveness of the species.
MF2453_2000_02
Keywords: MF2453; Environment and Natural Resources; MF